Enhancing Cotton Production and Sustainability through Multi-Tier Cropping Systems: Growth, Efficiency, and Profitability Analysis - Kanthan Thirukumaran; Kadapillai Nagarajan; Natarajan Vadivel; Vaddi Saitheja; Venkatesan Manivannan; Gnanasekaran Prabukumar; Panneerselvam Parasuraman; Muthusami Karuppasami Kalarani; Ramasamy Karthikeyan; Vaithiyanathan Sendhilvel (Agronomy, 2024)
Intercropping presents an opportunity to optimise land use and resource efficiency in cotton cultivation, particularly for small and marginal farmers facing climate-related challenges and rising input costs. This study explores the potential of intercropping short-duration vegetables with cotton to transform this production system into a more economically viable and sustainable one. The study was conducted in the Cotton Department of Tamil Nadu Agricultural University in Coimbatore during the winter irrigated season, from August to January, in both 2020 and 2021. The growth, yield parameters, equivalent yield (3645 and 4234 kg ha−1), and net return (Rs. 123,434 ha−1 and Rs. 154,034 ha−1) were higher in the intercropping system with the paired row planting of Bt cotton with two rows of cluster bean. Upon comparing sole cropping and the paired row method of planting, it was found that adopting the paired row system of planting Bt cotton with two rows of cluster bean was highly profitable in all aspects of crop production. Therefore, the adoption of paired row cropping systems with compatible intercrops that promote synergistic effects on the main crop should be considered for enhancing overall productivity, as well as sustainability.